METODE TILAWATI QUR’AN SEBAGAI UPAYA MENINGKATKAN SENI BACA QUR’AN - Elitawati Elitawati (LP3M IAI Al-Qolam Malang, 2022)
Abstract One of the sciences that must be known or learned by Muslims from an early age is the science of reading the Qur'an properly and correctly. The science of recitation is the science of studying the rules of reading the Qur'an. In addition to reading with the rules of recitation which of Makharijul letters and the nature of the letters must be really considered so as to avoid mistakes in pronunciation. In addition to reading with recitation, reading the Koran beautifully is also a sunnah practice. The art of reading the Koran beautifully can enhance the sound of reading the Koran. Therefor it’s important to know what are the rules for studying the science of recitation, the virtues of reading the Koran, and how the art of reading the Koran is. The virtue of reading the Koran is getting a reward from Allah SWT, and the rules of recitation that must be learned include the law of nunsukun or tanwin, mad law, qolqolah law, and so on. Then the art of reading the Koran is to read beautifully while still using the rules of tajwid so that it is not only beautiful to read but good and correct in the pronunciation of tajwid. Keywords: recitation, the art of reading the Qur'an